Strategic brand positioning analysis through comparison of cognitive and conative perceptions - Manhas, Parikshat S. (2010)
Due to the globalization of the economy, there has been great competition in the business sector. The basic human desire to challenge new limits and capture as much market as it is possible has given a new dimension to the concept of marketing - brand positioning. To position a brand requires making choices; whereas having a position means people will prefer a brand over another. A brand can be positioned in several ways: offering a specific benefit, targeting a specific segment, price or distribution. Despite the fact that positioning is considered by both academics and practitioners to be one of the key elements of modern marketing management, it is surprising to uncover general paucity of consumers/customers derived studies regarding brand positioning strategies. This article analyzes the market position held by a competitive set of brands in the hair oil market through a comparison of cognitive and conative perceptions. Cognition will be identified by trailing a factor analytic adaptation of importance performance analysis. In turn, conation will be gauged by stated intent of the consumers to purchase the hair oil brands under study. The alignment of the results from these techniques will help in identifying the position of leadership held by a brand in the hair oil market. The marketers, in order to strategically place their brands in today’s competitive market, need to identify the attributes on which they need to focus and those of paramount importance for the consumers. This method of positioning analysis offers a practical means for present-day marketers faced with the challenge of identifying one or few brands from their diverse and multi-attributed brand range that could be developed to differentiate their brand in a meaningful way to consumers.